2021
DOI: 10.1167/tvst.10.13.24
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Subclinical Microvascular Biomarkers in Coronary Heart Disease in Retinal Imaging

Abstract: Purpose Cardiovascular disease and foremost coronary heart disease (CHD) are the worldwide leading causes of death. The aim of this study was to use non-invasive, multimodel retinal imaging to define microvascular features in patients with and without coronary angiography (CA)-confirmed CHD. Methods In this prospective, cross-sectional pilot study we included adult patients who presented to a tertiary referral center for elective CA due to suspected CHD. All patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Individuals exhibiting lower retinal vascular density show inconsistent signs of systemic vascular disease and are more frequently associated with a medical history of peripheral artery disease, CAD, high blood pressure, and type 2 diabetes mellitus. The microvascularization of the retina is closely linked to the cardiovascular risk profile and the severity of coronary lesions [34].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals exhibiting lower retinal vascular density show inconsistent signs of systemic vascular disease and are more frequently associated with a medical history of peripheral artery disease, CAD, high blood pressure, and type 2 diabetes mellitus. The microvascularization of the retina is closely linked to the cardiovascular risk profile and the severity of coronary lesions [34].…”
Section: Discussionmentioning
confidence: 99%
“…Aschauer J. examined coronary heart disease patients with a control group and findings were similar. They observed a trend of reduced VD in the total retina, as well as the individual retinal capillary plexuses (superficial and deep) and the choriocapillaris layer in patients with significant CHD, but neither these results nor logistic regression analysis were significant [ 37 ]. Wang et al also reported that CAD patients have significantly decreased VD [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study examined 45 patients undergoing elective coronary angiography and OCTA. Patients with coronary heart disease confirmed using elective coronary angiography had a significantly lower VD in the SCP, DCP, and choriocapillaris [34]. Additionally, an observational study by Matuleviciute et al [35] demonstrated a significantly decreased risk of three-vessel CAD with increased VD [35].…”
Section: Atherosclerotic Diseasementioning
confidence: 95%